La médecine entre académie et université en Sicile au XVIIe siècle - Delphine Montoliu (Les Dossiers du GRIHL)
Most Sicilian institutions in early modern period were not interested in the new scientific knowledge promoted by the academies of Lincei in Rome, Cimento in Florence and Investiganti in Naples, but they however prioritized medicine, because of the numerous epidemics in the island: while the Senate of Messina recognized the usefulness of science and encouraged scholars in their studies, the academicians in Palermo were muzzled by the Spanish power. So Catania, which had only literary academies, competed scientifically with Messina thanks to its university founded in 1434. The birth of a university in Messina in 1596, in addition to its academies including the multidisciplinary Fucina, then set the city in an awkward position with Catania which wanted to maintain its scientific monopoly and with Palermo which failed to obtain the agreement of the authorities to create its own university. Medicine was a concrete example of this dichotomy between academy and university, and therefore of this structural problem of knowledge because it highlighted the coexistence of a parallel cultural system, alternative to state universities.